2021
DOI: 10.3389/fenrg.2021.710766
|View full text |Cite
|
Sign up to set email alerts
|

Review of Large-Scale Biochar Field-Trials for Soil Amendment and the Observed Influences on Crop Yield Variations

Abstract: Increasing pressure on farming systems due to rapid urbanization and population growth has severely affected soil health and fertility. The need to meet the growing food demands has also led to unsustainable farming practices with the intensive application of chemical fertilizers and pesticides, resulting in significant greenhouse gas emissions. Biochar, a multifunctional carbon material, is being actively explored globally for simultaneously addressing the concerns related to improving soil fertility and miti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 189 publications
(254 reference statements)
3
25
0
1
Order By: Relevance
“…This may be why there was no positive response to soil conditioners in the olive yield in a short-term assessment. These observations substantiate the requirement of long-term soil amendments application field trials to accurately analyse its effects on crop yield and soil quality [36]. The effects of soil treatments on the biometric variables of fruits obtained from the harvests of 2018 and 2019 are also shown in Table 3.…”
Section: Effect Of Soil Treatments On Olive Yield Fruit Biometric Var...supporting
confidence: 73%
See 2 more Smart Citations
“…This may be why there was no positive response to soil conditioners in the olive yield in a short-term assessment. These observations substantiate the requirement of long-term soil amendments application field trials to accurately analyse its effects on crop yield and soil quality [36]. The effects of soil treatments on the biometric variables of fruits obtained from the harvests of 2018 and 2019 are also shown in Table 3.…”
Section: Effect Of Soil Treatments On Olive Yield Fruit Biometric Var...supporting
confidence: 73%
“…Applying zeolites and biochar had no significant effect on crop yield in both years. Similarly, a lack of a substantial impact on crop yield by the short-term use of zeolites and biochar was reported by some authors [34][35][36]. Haider [37] showed that biochar needs a certain degree of ageing in the soil to affect the crop yield positively.…”
Section: Effect Of Soil Treatments On Olive Yield Fruit Biometric Var...mentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, several field studies demonstrated that applying biochar to agricultural soil significantly reduced nitrate, potassium, phosphorous, magnesium, sodium, and calcium leaching (Vijay et al 2021 ). Li et al ( 2019a ) reported that tobacco stems were pyrolysed to produce biochar.…”
Section: Agronomymentioning
confidence: 99%
“…It has been assessed that biochar carbon and nutrient contents depend on the organic material contained in the original biomass feedstock used for its production, while biochar surface chemical properties as well as pore size depend more on the pyrolysis temperature ( Lei and Zhang, 2013 ; Zhao et al, 2013 ). In addition, the effects of biochar application may vary between laboratory-scale and field-based studies and across different agroclimatic zones ( Vijay et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%